Further purification and characterization of heat-stable enterotoxin produced by Yersinia enterocolitica. - Okamoto, K (1982)
Heat-stable enterotoxin (ST) of Yersinia enterocolitica was produced under defined conditions. It was first detected in the culture supernatant of the late-logarithmic phase of growth and increased lineally during the the stationary phase of growth. The ST level became maximum at the decline phase of growth, and the ST was not detected in the lysate of bacteria obtained from the decline phase of growth. The ST was extensively purified from the culture supernatant, and about a 1,905-fold purification was achieved with a yield of 8.9%. The minimal effective dose of the purified ST was approximately 25 ng in the suckling mouse assay. The purified ST gave a single 280-nm absorbing peak on polyacrylamide disc gel electrophoresis and had a maximum absorption at 272 nm, and its molecular weight was 9,700 by Sephadex G-75 superfine gel filtration. The biological activity of the purified ST was lost by treatment with 2-mercaptoethanol, suggesting that the ST contained disulfide bridges in the molecule which were required for the development of toxic activity. The purified ST was heat stable at 100 degrees C for 10 min between pH 2.2 and 8.0, but not at pH values greater than 9.0 or in 2 N HCl. The treatment of the ST with trypsin resulted in a retarded elution of the ST activity by Sephadex F-75 superfine gel filtration and a passage through a UM-20 membrane filter.